Composition and assembly of the bacterial community in the overlying waters of the coral reef of China’s Xisha Islands - Liu, Si-Jia; Xie, Zhang-Xian; Wu, Peng-Fei; Zheng, Ru-Wen; Liu, Yuan; Lin, Lin; Liu, Hai-Peng; Wang, Da-Zhi (Frontiers in Microbiology, 2022)
Coral reef ecosystems are one of the most diverse and productive habitats on Earth. Microbes in the reef-overlying waters are key players in maintaining this ecosystem through regulating biogeochemical and ecological processes. However, the composition structure and assembly mechanism of microbial community in the reef-overlying waters remain largely unknown. In the present study, the bacterial communities from the overlying waters of atolls and fringing reefs as well as the surface waters of the adjacent open ocean of the Xisha Islands in the South China Sea were investigated using 16S rRNA high-throughput sequencing combined with a size-fractionation strategy. The results showed that environments of all sampling stations were similar, characterized by an almost complete lack of inorganic nutrients such as nitrogen and phosphorus. Proteobacteria, Cyanobacteria and Bacteroidetes were the dominant phyla, and Synechococcus was most abundant at the genus level in both large fraction (LF; 1.6-200 µm) and small fraction (SF; 0.2-1.6 µm) communities. Only a slight difference in community composition between LF and SF samples was observed. The bacterial communities among the three habitat types showed noticeable differences, and the bacterial composition among the atoll reefs was more varied than that among the fringing reefs. The similarity of bacterial communities significantly declined with the increasing geographic distance, and stochastic processes were more important than deterministic processes in bacterial community assembly. This study sheds lights on the bacterial biodiversity of coral reefs and the importance of stochastic process in structuring bacterial communities.